2014
DOI: 10.4103/0973-1482.138100
|View full text |Cite
|
Sign up to set email alerts
|

Oral squamous cell carcinoma in a South African sample: Race/ethnicity, age, gender, and degree of histopathological differentiation

Abstract: OSCC was diagnosed at a younger age in black than in white persons; the proportion of black males in the black population group was greater than that of white males in the white population group; and the proportion of SCC of the lips was higher in younger than in older persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Our data's gender distribution was comparable with the Pakistani and African population [13,17]; however, the male predilection was observed up to 4.3:1 in multicenter studies involving larger sample data [12,16]. These findings are in accordance with multiple studies conducted to associate the age [13][14][15][16] and gender factors [15,[17][18][19][20] with the increasing risk of developing OC.…”
Section: Socio-demographic Featuressupporting
confidence: 90%
See 2 more Smart Citations
“…Our data's gender distribution was comparable with the Pakistani and African population [13,17]; however, the male predilection was observed up to 4.3:1 in multicenter studies involving larger sample data [12,16]. These findings are in accordance with multiple studies conducted to associate the age [13][14][15][16] and gender factors [15,[17][18][19][20] with the increasing risk of developing OC.…”
Section: Socio-demographic Featuressupporting
confidence: 90%
“…In Malaysia and Indonesia, betel quid chewing habit has been primarily replaced with smoking since early to mid-1990s [23]. The second most common tumor site within the oral cavity included parotid and submandibular glands, which was also found to be in opposition to several other studies [12,[18][19][20].…”
Section: Socio-demographic Featuresmentioning
confidence: 94%
See 1 more Smart Citation
“…This suggests that estrogen deficiency may play a role in the pathogenesis of OSCC in some women. [ 22 ] Due to the increase in the incidence of oral cancer in females, in our study, we found the higher metastatic potential was associated with high-grade tumor buds, Type V ITF pattern, and poorly differentiated OSCC.…”
Section: Discussionmentioning
confidence: 59%
“…Differences between genders regarding some anatomical variations ( 1 ), and the incidence and behavior of diseases are well documented in medicine ( 2 – 5 ) as well as in dentistry the differences between males and females regarding root morphology ( 6 , 7 ) and the association with some diseases were also reported ( 8 , 9 ). In the dental literature, many anatomical studies addressed different variations in root canal morphology according to ethnic background ( 10 18 ), while, scarce and inconclusive information are available regarding gender impact on teeth morphology ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%